A Penentuan Parameter Desain Mesin Perontok Sorgum Berdasarkan Karakteristik Fisik dan Mekanik Tanaman Sorgum: Identification of the Physical Characteristics of Sorghum Bioguma for the Design of a Sorghum Thresher Machine - Ana Nurhasanah; Wawan Hermawan; Tineke Mandang; Astu Unadi; Maria TJB; Herry Susanto; Arif S; M Hidayat; Suparlan Suparlan; Anugerah Fitri Amalia; Teguh WW; Uning B; Ni Putu Dian Nitamiwati; Adji P (Jurnal Keteknikan Pertanian, 2023)
An effective and efficient threshing mechanism for sorghum plants requires information about technical properties, including the physical and mechanical properties of this sorghum plant. This study aims to determine some of the physical properties of the sorghum variety Bioguma in the seeds, stems, and leaves for the threshing mechanism of the sorghum seeds and stems. This study used a descriptive method with several repetitions from 3 to 30, depending on the measured parameters. All sampling was done randomly. The sorghum plants tested were from several fields in Majalengka and Bogor. The dimensions of the Bioguma variety of sorghum seeds, which have values ranging from 4.23 mm to 5.88 mm in width, 2.49 mm to 2.85 mm in thickness, and 3.95 mm to 4.98 mm in height, are considered in the design of threshing cylinder sieve sizes, namely using a perforated plate with a diameter of 6 mm; threshing power requirements with threshing cylinder speed on the designed threshing machine, assuming a threshing cylinder diameter of 51 cm and a rate of 700 rpm requires a power of 9.17 kW.